Developing tourist attraction strategies in the Museum of Decorative Arts of Iran, Isfahan - Maedeh Barati; Marzieh Hekmat; Neda Torabi Farsani (اقتصاد شهری)
Museums today are established within cities in line with socio-cultural equity, serving as accessible gateways for all citizens to understand and engage with human life and the surrounding environment. Although these institutions differ in subject, scale, quality, and function, they all strive to identify and attract the largest possible audiences and to improve their service delivery. The Museum of Decorative Arts of Iran, housed in the Rakeb-Khaneh Palace in Isfahan, despite its cultural, historical, and geographical advantages, suffers from a shortage of visitors compared to competing museums. This study aims to develop effective strategies to attract a larger audience to this museum by identifying the factors contributing to this challenge and proposing operational solutions. The main research problem is to investigate the reasons behind the museum’s low attendance and to identify suitable strategies for increasing visitor numbers. The research questions include identifying the museum’s internal strengths and weaknesses, as well as its external opportunities and threats, determining its strategic position, and proposing practical measures to attract audiences. This study employs a qualitative case-study approach, and data were collected through semi-structured interviews and questionnaires involving experts in museum studies. A SWOT analysis revealed that the museum is in a “conservative” strategic position, indicating that, despite numerous external opportunities, internal weaknesses have hindered the full realization of its potential. The results led to the proposal of strategies such as market development (creating an independent database, launching a website, and informing tour guides), market penetration (designing catalogs, using billboards, and organizing thematic exhibitions), product development (providing digital content, specialized tours, and enhanced amenities), and horizontal integration (holding joint exhibitions and offering combination tickets). These strategies, emphasizing audience needs and reinforcing the museum’s ties with the community, not only help revitalize the Museum of Decorative Arts of Iran but also contribute to the vitality of Isfahan’s urban tourism economy. By providing an operational framework, this research fills a gap in the existing literature and enriches the knowledge base of museum marketing.